2019
DOI: 10.1056/nejmoa1805435
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Ebola Sequelae in Liberia

Abstract: BACKGROUND Multiple health problems have been reported in survivors of Ebola virus disease (EVD). Attribution of these problems to the disease without a control group for analysis is difficult. METHODS We enrolled a cohort of EVD survivors and their close contacts and prospectively collected data on symptoms, physical examination findings, and laboratory results. A subset of participants underwent ophthalmologic examinations. Persistence of Ebola virus (EBOV) RNA in semen samples from survivors was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 26 publications
7
81
0
Order By: Relevance
“…As such, abandonment of abstinence and/or condoms can be expected after negative testing, and while in our study only 15% of men with an undetectable EBOV RNA semen result followed such a pattern, it is important to recognize the limitations of EBOV RNA testing of semen including variability in the lower limit of detection across assays and an incomplete understanding of the threshold below which infection is not possible-information that was shared with participants via post-test counseling with opportunities to ask questions to ensure understanding. We and others have also shown that detection of EBOV RNA in semen can be intermittent and can follow repeatedly undetectable tests [7], [18]. In particular, 5 of the 13 men in our cohort who ultimately tested positive had an initial negative test.…”
Section: Discussionsupporting
confidence: 57%
“…As such, abandonment of abstinence and/or condoms can be expected after negative testing, and while in our study only 15% of men with an undetectable EBOV RNA semen result followed such a pattern, it is important to recognize the limitations of EBOV RNA testing of semen including variability in the lower limit of detection across assays and an incomplete understanding of the threshold below which infection is not possible-information that was shared with participants via post-test counseling with opportunities to ask questions to ensure understanding. We and others have also shown that detection of EBOV RNA in semen can be intermittent and can follow repeatedly undetectable tests [7], [18]. In particular, 5 of the 13 men in our cohort who ultimately tested positive had an initial negative test.…”
Section: Discussionsupporting
confidence: 57%
“…A prospective, controlled study of survivors of EVD who had attended the EVD survivors clinic at 34 Military Hospital in Freetown, Sierra Leone, or other medical facilities in the region and reported ophthalmic symptoms since discharge was conducted in 2016. 5 All participants of this study who attended between January 22, 2016, and April 26, 2016, were contacted by telephone and invited to attend the ophthalmology clinic for review 1 year following their baseline examination. The study was approved by the Sierra Leone Ethics and Scientific Review Committee and followed the tenets set forth by the World Medical Association Declaration of Helsinki, seventh revision (2013).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…4 A retinal lesion specific to Ebola was identified in 15% of previously symptomatic survivors. 5,6 Lesions were predominantly nonpigmented, with a pale-gray appearance. Their shapes are variable, but sharp angulations are characteristic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The program aimed to mitigate the risk for EVD reintroduction from exposure to survivors' body fluids. We were able to enroll ≈90% of the survivors in Guinea and test the semen of >90% of the enrolled male survivors >15 years of age, an unprecedented rate compared with other survivor monitoring programs (19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%